On guilt and the depoliticization of downsizing practices - Karfakis, Nikolaos; Kokkinidis, George (My University, 2019)
The purpose of this paper is to provide a theoretical conceptualisation of guilt and the depoliticization of downsizing practices. The authors begin with a critical review of the relevant management literature aiming to establish the discursive normalization and individualization of (un)employment. The authors then use secondary sources to reflect on the downsizing process. A process that, as the authors argue, is distinguished into three separate but interconnected phases: corporate memos (phase 1), termination scripts (phase 2) and the role of outplacement services (phase 3). By examining this process, the aim is to point to the mechanisms through which downsizing practices are neutralized and depoliticized. Design/methodology/approach: This is a conceptual work that provides a systematic overview of the existing management literature on downsizing and guilt. Use of other secondary sources (corporate memos and termination scripts) is also employed to draw links between the discursive normalization of downsizing as identified in the relevant literature and the specific organizational processes and practices implemented by corporations during downsizing. The authors identify common ideas and themes that cut across the relevant literature and the secondary sources and aim to offer a theoretical conceptualisation of guilt and the depoliticization of downsizing practices. Findings: This paper argues that downsizing discourses and practices contribute to the feelings of personal responsibility and self-blame, reinforcing an individualistic understanding of work and unemployment that excludes more structural ones, and that it helps in reproducing the existing structures of power. Research limitations/implications: The study recognizes that employees’ reactions are not only unpredictable but also constantly evolving, depending on personal and social circumstances. The authors also recognize that the work is based on secondary sources much of which talk about practices in US companies, and thus the authors are and should be cautious of generalizations. The authors hope, however, that the authors will encourage further empirical research, particularly among organization studies and critical management scholars, on downsizing practices and guilt. For the authors’ part, the authors have tried to offer a critical reflection on how guilt is produced through corporate discourses and practices, and the authors believe that further empirical investigation on the three phases of the downsizing process (as identified in our work) and the lived experience of (un)employment is needed. As corporate downsizing discourses and practices frame (un)employment in strictly individualist and behavioral terms, the authors wish to emphasize the need for further theoretical investigation and political contestation. The authors, therefore, hope that the work will contribute to the relevant literature on downsizing practices and open up the discussions around layoff policies and the structural conditions of (un)employment. Originality/value: The paper shows that downsizing practices and feelings of guilt are strongly linked to and exemplify the “individualization” of social and political issues such as work and unemployment. The authors suggest that individualization signifies, in some sense, a retreat from organized collective resistance and mobilization based upon class and that the prevalence of the ideology of individualism (and its correlative, meritocracy), over alternative explanations and solutions to such public issues, helps in reproducing existing structures of power and inequity.
Keywords: Downsizing; Guilt; Individualization; Unemployment